THE IMPLEMENTATION BLENDED LEARNING METHOD USING ARTICULATED STORYLINE IN CLASS 4 FRACTION LEARNING, MUHAMMADIYAH PRIMARY SCHOOL, PANGKALPINANG - fandi nugroho; Muhammad Iqbal Arrosyad (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
This study aims to describe the implementation of multimedia learning in blended learning in mathematics in grade 4 elementary schools on the topic of fractions. Articulated storyline is an effective medium for elementary school students that is easily developed as one of the multimedia blended learning used in the blended learning method. In our research we examined how the impact of implementation blended learning using multimedia articulated storylines, In this case, it is also discussed how the influence of multimedia articulation storylines as one of the multimedia that can be developed easily to help teachers in distance learning, especially mathematics learning in schools. Primary school related to fraction learning. In this research, students are taught how to interpret the understanding of the concept of fraction problems and proof in life related to mathematics learning problems, so that they can describe mathematical problems and can understand the concept of fractions using logical reasoning so that they are able to prove reasoning about fraction problems according to their abilities. The use of reasoning is needed to determine the concepts that have been made based on the understanding of the concept of fractions that the students have. This study was designed to see the effect of blended learning which is applied as a learning model used to teach logical reasoning in mathematics learning, especially about fraction problems, and how the effect of the application of blended learning on learning outcomes of primary school students at Muhammadiyah Elementary School Pangkalpinang